Drag Reduction On Naca 2412 Using Dimpled Airfoil And Grooved Wing - Gracia, Samuel Merryisha Sweety (2020)
The competitiveness of high-performance wing with improved stalling characteristics gains more popularity in recent decades. The primary factor dominating the lack in aerodynamic performance is drag formation. Rough surface aerodynamics is one of the promising alternative method which involves passive control technique to degrade drag and improve lift to drag ratio. In current study, the interaction of dimple and groove parameters influencing the aerodynamic performance of airfoil and wing at a different angle of attack operating at 30 m/s and Reynolds number of 4.4x105 are considered. The present study divides into two, Study (1) explores the aerodynamic performance and behaviour of five different indented and protruded dimples located at 1) 0.3C, 2) 0.5C, 3) 0.7C, 4) multiple dimples on suction side alone and 5) multiple dimples indenting throughout airfoil (i.e. both pressure and suction side) over 2D airfoil. Study (2) deals with grooves indented over the wingspan at different x/c location 1) near leading edge (0.2C), 2) near trailing edge (0.8C), 3) mid-span (0.5C), 4) triplet location (0.2C, 0.5C, 0.8C). Altering the surface of airfoil/wing boosts its efficiency, thereby thickens the reattached flow; hence the flow is kept attached even at higher AOA. The models are designed using CATIA V5R20 and ANSYS Fluent helps to simulate the flow behaviour, and aerodynamic performance difference between models. The results of study (1) show introducing dimples over airfoil keep flow attached beyond 0.25C even at 16o AOA with (l/d)max of 39.5% enhancement. The results of the study (2) show that the presence of grooves enhances the stalling characteristics by keeping the flow attached up to 18o AOA. In all the grooved wing model, the L/D shows at least 0.05% improvement compared to baseline wing. However, the aerodynamic characteristics show the pronounced result on SRD(I) 0.5, SOD(P) 0.3, SSRD(I), SSSD(I) and SSSD(P) models in the case of dimple airfoil study and triplet groove wing in the case of groove wing study. The analyses of the dimpled airfoil and groove wing with different configurations showcased the sensitivity of flow over rough airfoil on pressure and suction side.